2005
DOI: 10.1071/rd05066
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and reliable chemically assisted enucleation method for handmade cloning in cattle

Abstract: The purpose of the present study was to find an efficient and reliable chemically assisted procedure for enucleation related to the handmade cloning (HMC) technique. After in vitro maturation oocytes were incubated in 0.5 microg mL(-1) demecolcine for 2 h. Subsequently, zonae pellucidae were digested with pronase, and one-third of the cytoplasm connected to an extrusion cone was removed by hand using a microblade. The remaining two-thirds were used as recipients for HMC, and reconstructed and activated embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
2
26
0
6
Order By: Relevance
“…The enucleation can be accurately achieved based on the visible membrane protrusion. Vajta et al obtained high cloning efficiency with a 48% blastocyst rate by treating bovine oocytes with demecolcine [13]. Tani et al reported that treating bovine oocytes with demecolcine for over 30 min caused protrusions in the cell membrane and enhanced MPF activity in the oocytes during the process [14].…”
Section: Discussionmentioning
confidence: 99%
“…The enucleation can be accurately achieved based on the visible membrane protrusion. Vajta et al obtained high cloning efficiency with a 48% blastocyst rate by treating bovine oocytes with demecolcine [13]. Tani et al reported that treating bovine oocytes with demecolcine for over 30 min caused protrusions in the cell membrane and enhanced MPF activity in the oocytes during the process [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several chemicals, including etoposide (Fulka and Moor, 1993;Elsheikh et al, 1997Elsheikh et al, , 1998Karnikova et al, 1998) and demecolcine (Gasparrini et al, 2003;Ibanez et al, 2003;Vajta et al, 2005), have been utilized to chemically induce or assist oocyte enucleation. Previously, attempts have been made to combine zonae-free manipulation with chemically induced or assisted enucleation in sheep and cattle (Peura, 2003;Vajta, 2005). According to Yin et al (2002a,b), the exposure of in vitro matured porcine oocytes to demecolcine results in an extrusion cone containing a condensed chromosome mass, which can be removed in TC.…”
Section: Introductionmentioning
confidence: 98%
“…Micromanipulator was routinely used to produce somatic cell cloned embryos in animals (Lagutina et al, 2007). However, the zona-free handmade cloning (HMC) technology is a preferred choice, with a higher success rate in producing cloned offspring in different species viz., horses (Lagutina et al, 2007), cattle Vajta et al, 2005), pig (Du et al, 2005) and buffalo (Shah et al, 2008). Handmade cloning (HMC) technique in goat is very significant on two accounts.…”
Section: Introductionmentioning
confidence: 99%